Sie sind auf Seite 1von 10

www.sakshieducation.

com

2.MATHEMATICAL INDUCTION
Principle of finite Mathematical Induction:

Let {P(n) / n ∈ N} be a set of statements. If (i) p(1) is true


(ii) p (m) is true ⇒ p (m+1) is true ; then p (n) is true for every n ∈ N.
Principle of complete induction:
Let {P (n) / n N} be a set of statements. If p (1) is true and p(2), p(3) .... p (m-1) are true => p(m)
is true, then p (n) is true for every n ∈ N.

Note:
(i) The principle of mathematical induction is a method of proof of a statement.
(ii) We often use the finite mathematical induction, hence or otherwise specified the mathematical
induction is the finite mathematical induction.
Some important formulae:
n ( n + 1)
1. ∑ n =
2
n ( n + 1)( 2n + 1)
2. ∑n 2
=
6
;

n 2 ( n + 1)
2

3. ∑ n =3

4
4. a, ( a + d ) , ( a + 2d ) ,.............. are in a.p
n n
n th term tn = a + ( n −1) d , sum of n terms S n = ⎡⎣ 2a + ( n − 1) d ⎤⎦ = [ a + l ] ,
2 2
a = first term, l= last term.
5. a, ar , ar 2 ,........ is a g.p.
Nth term tn = a.r n−1 . a = 1st term, r = common ratio.

=a
(r n
− 1)
; r > 1,
⎛ 1− rn ⎞
Sum of n terms sn = a⎜ ⎟; r < 1
r −1 ⎝ 1− r ⎠

www.sakshieducation.com
www.sakshieducation.com
Using mathematical induction prove the following

n(n + 1)(2n + 1)
1. 12 + 22 + 32 + ..... + n 2 =
6
Sol: Let Sn be the given statement
For n = 1 L.H.S = 1
1(1 + 1)(2 + 1)
R.H .S = =1
6
L.H.S = R.H.S
∴ S (1) is true
Assume Sk is true
k (k + 1)(2k + 1)
11 + 22 + 32 + .... + k 2 =
6
Adding (k + 1) term on both sides i.e. (k + 1) 2 on both sides
th

k (k + 1)(2k + 1)
12 + 22 + 32 + .... + k 2 + (k + 1)2 = + (k + 1) 2
6
⎧ k (2k + 1) + 6(k + 1) ⎫
= (k + 1) ⎨ ⎬
⎩ 6 ⎭
(k + 1){2k + 7k + 6}
2
=
6
(k + 1) (k + 2) (k + 3)
=
6
(k + 1) {(k + 1) + 1}{2(k + 1) + 1}
=
6
∴ Sk +1 is true
∴ Sn is true

n(n 2 + 6n + 11)
2. Prove that 2.3+ 3.4 + 4.5+ …. Up to n terms
3
Sol: 2, 3, 4………………… n terms tn = 2 + (n − 1)1 = n + 1
3, 4, 5……….. n terms tn = 3 + (n − 1)1 = n + 2
n(n 2 + 6n + 11)
2.3 + 3.4 + 4.5 + ......... + (n + 1)(n + 2) =
3
Let Sn be the given statement
For n = 1 L.H.S = 2.3 = 6
1(1 + 6 + 11)
R.H .S = =6
3
L. H.S = R.H.S
∴ S (1) is true
Assume Sk is true
k (k 2 + 6k + 11)
∴ 2.3 + 3.4 + 4.5 + ....... + ( k + 1)( k + 2) = + ( k + 2)( k + 3)
3
k (k 2 + 6k + 11) + 3(k 2 + 5k + 6)
=
3

www.sakshieducation.com
www.sakshieducation.com
k 3 + 9k 2 + 26k + 18
=
3
1 9 26 18
(k + 1) {k 2 + 8k + 18} k = −1
= 0 −1 −8 −18
3
1 8 18 0
(k + 1) {(k + 1) + 6(k + 1) + 11}
2

=
3
∴ Sk +1 is true
Hence S ( n ) is true for all n ∈ N

1 1 1 1 n
3. + + + ..... + =
1.3 3.5 5.7 (2n − 1)(2n + 1) 2n + 1
Sol: Let S ( n ) be the given statement
1 1
For n = 1 L.H.S =
1.3 3
1 1
R.H.S = =
2 +1 3
Assume Sk is true
1 1 1 1 k
+ + + ..... + =
1.3 3.5 5.7 (2k − 1)(2k + 1) 2k + 1
1
Adding (k + 1)th term i.e. on both sides
(2k + 1)(2k + 3)
1 1 1 1 1 k 1
+ + + ...... + + = +
1.3 3.5 5.7 (2k − 1)(2k + 1) (2k + 1)(2k + 3) 2k + 1 (2k + 1) (2k + 3)
k (2k + 3) + 1
=
(2k + 1)(2k + 3)
2k 2 + 3k + 1
=
(2k + 1)(2k + 3)
k +1
=
2k + 3
∴ Sk +1 is true
Hence S ( n ) is true for all n ∈ N

4. 43 + 83 + 123 + .... up to n terms = 16n 2 (n + 1) 2


Sol: Let S ( n ) be the given statements
For n = 1 L.H .S = 43 = 64
R.H.S = 16(1)2 (1 + 1)2 = 64
∴ L.H.S = R.H.S
Hence S (1) is true
Assume S ( k ) is true
∴ 43 + 83 + 123 + .... + (4k )3 = 16 k 2 (k + 1) 2
Adding {4(k + 1)} on both sides
3

www.sakshieducation.com
www.sakshieducation.com

43 + 83 + 123 + ... + (4k )3 + {4(k + 1)} = 16k 2 (k + 1)2 + 64(k + 1)3


3

43 + 83 + 123 + ..... + {4(k + 1)} = 16(k + 1) 2 {k 2 + 4k + 4}


3

= 16(k + 1) 2 (k + 2) 2
∴ Sk +1 is true
Hence S ( n ) is true for all n ∈ N

n
5. a + (a +d) +(a +2d) + ….up to n terms a = [ 2a + (n − 1)d ]
2
n
Sol: a + (a + d ) + (a + 2d ) + .... + [ a + (n − 1)d ] = [ 2a + (n − 1)d ]
2
Let S ( n ) be the given statement
For n = 1
L.H.S. = a
1
R.H.S = [ 2a + (1 − 1)d ] = a
2
L.H.S. = R.H.S
Assume Sk is true
k
a + (a + d ) + (a + 2d ) + ..... + a + (k − 1)d + (a + kd ) = [ 2a + (k − 1)d ] + (a + kd )
2
k
a + (a + d ) + .... + a + kd = ak + (k − 1)d + a + kd
2
⎧k ⎫
= a ( k + 1) + d ⎨ ( k − 1) + k ⎬
⎩2 ⎭
⎧ k −1+ 2 ⎫
= a ( k + 1) + kd ⎨ ⎬
⎩ 2 ⎭
⎛ k +1⎞
=⎜ ⎟ {2a + ( kd )}
⎝ 2 ⎠
∴ Sk +1 is true
Hence Sn is true for all n ∈ N

a(r n − 1)
6. a + ar + ar 2 + .......... upto n terms = (r ≠ 1)
r −1
a(r n − 1)
Sol: a + ar + ar 2 + .......ar n−1 =
r −1
Let S ( n )be the given statement
For n = 1
L.H.S = a
a(r − 1)
R.H.S = =a
(r − 1)
∴ L.H.S = R.H.S
∴ S (1) is true
Assume Sk is true
a(r k − 1)
∴ a + ar + ar 2 + .......ar k −1 =
r −1

www.sakshieducation.com
www.sakshieducation.com
Adding a.r k on both sides
a(r k − 1)
a + ar + ar 2 + ............ + ar k −1 + ar k = + ar k
r −1
a {r − 1 + r k +1 − r k }
k

a + ar + ar 2 + ............ + ar k =
r −1
k +1
a(r − 1)
=
r −1
Hence S k +1 is true
∴ Sn is true ∀n ∈ N

n( Sn − 1)
7. 2 + 7 + 12 + ......... + (5n − 3) =
2
Sol: Let S ( n ) be the given statement
For n = 1
L.H.S =2
1(5 − 1)
R.H.S = =2
2
∴ L.H.S = R.H.S for n = 1
Hence S (1) is true
Assume S ( k ) is true
k (5k − 1)
2 + 7 + 12 + ...... + (5k − 3) =
2
5k 2 + 9k + 4 (k + 1) {5(k + 1) − 1}
= =
2 2
⇒ S k +1 is true
Hence S ( n ) is true ∀n ∈ N

8. 4 n − 3n − 1 is divisible by 9
Sol: Let S ( n ) be the given statement i.e. S( n) = 4n − 3n −1
For n = 1 ⇒ S (1) = 4 − 3 − 1 = 0 is divisible by 9
Assume S ( k ) is true i.e. 4k − 3k − 1 is divisible by 9
S k +1 = 4 k +1 − 3( k +1) − 1 = 4 k .4 − 3k − 4
= {9m + 3k + 1} 4 − 3k − 4
= 36 m + 12 k + 4 − 3k − 4
= 36m + 9k = 9{4m + k} this is
Divisible by 9
Hence S k +1 is divisible by 9
∴ Sn is divisible by 9 ∀n ∈ N

www.sakshieducation.com
www.sakshieducation.com
9. Show that 3.52 n +1 + 23n +1 + 23n +1 is divisible by 17
Sol: Let S( n ) = 3.52 n+1 + 23n+1 be the given statement
S(1) = 3.53 + 24 = 375 + 16 = 391 = 17 × 23
This is divisible by 17
Assume Sk is true
S k = 3.5 2 k +1 + 23 k +1 is divisible by 17
Let 3.52 k +1 + 23k +1 = 17 m
3.52 k +1 = 17m − 23k +1
S k +1 = 3.5 2 k + 3 + 23 k + 4
= 3.52 k +1.2 + 23k +1.23
= 25 {17 m − 23k +1} + 23k +1.8
= 25 × 17 m − 17(23k +1 ) = 17 {25 m − 23k +1} is divisible by 17
Hence S k +1 is true
∴ Sn is true for all n ∈ N

n(n + 1)(n + 2)(n + 3)


10. 1.23.+2.3.4+3.4.5+……….up to n terms =
4
n(n + 1)(n + 2)(n + 3)
Sol: 1.2.3 + 2.3.4 + 3.4.5 + .......... + n(n + 1)(n + 2) =
4
Let S ( n ) be the given statement
For n = 1
L.H.S = 1.2.3 = 6
1(2)(3)(4)
R.H.S = =6
4
Assume S ( k ) is true
k (k + 1)(k + 2)(k + 3)
1.2.3 + 2.3.4 + 3.4.5 + ......... + k ( k + 1)( k + 2) =
4
Adding (k + 1) (k + 2) (k + 3) on both sides

k (k + 1)(k + 2)(k + 3)
∴1.2.3 + 2.3.4 + 3.4.5 + ......... + k (k + 1)(k + 2) + (k + 2)(k + 2)(k + 3) =
4
S k +1 is true
Hence S ( n ) is true ∀ n ∈ N

13 13 + 23 13 + 23 + 33 n
11. + + + ...... upto n terms = [2n 2 + 9n + 13]
1 1+ 3 1+ 3 + 5 24
1 1 +2 1 +2 +3
3 3 3 3 3 3
1 + 2 + 33 + ..... + n3
3 3
n
Sol: + + + .............. + = ⎡⎣ 2n 2 + 9n + 13⎤⎦
1 1+ 3 1+ 3 + 5 1 + 3 + 5 + .... + (2n − 1) 24
Let S ( n ) be the given statement
For n = 1
13
L.H.S = = 1
1
1
R.H.S = = [2 + 9 + 13] = 1
24
www.sakshieducation.com
www.sakshieducation.com
L.H.S = R.H.S
Hence S (1) is true
Assume Sk is true
13 13 + 23 13 + 23 + 33 13 + 23 + 33 + ....... + k 3 k
∴ + + + .... + = ⎡⎣2k 2 + 9k + 13⎤⎦
1 1+ 3 1+ 3 + 5 1 + 3 + 5 + .....2(k − 1) 24
13 13 + 23 13 + 23 + 33 k 2 (k + 1) 2 k
+ + + .... + = ⎡⎣ 2k 2 + 9k + 13⎤⎦
1 1+ 3 1+ 3 + 5 4k 2
24
(k + 2) 2
Adding on both sides
4
13 13 + 23 13 + 23 + 33 (k + 1) 2 (k + 2) 2 k (k + 2) 2
+ + + ..... + + = {2k + 9k + 13} +
2

1 1+ 3 13 + 5 4 4 24 4
1 1 +2 1 +2 +3
3 3 3 3 3 3
(k + 2) 2 k {2k + 9k + 13} + 6(k + 4k + 4)
2 2

+ + + .... + =
1 1+ 3 13 + 5 4 24
2k + 9k + 13 + 6k + 24k + 24
2 2
=
24
2k + 15k + 37 k + 24
2 2
=
24
2 15 37 2
k = −1
0 −2 −13 −24
2 13 24 0
(k + 1) {(2k + 13k + 24}
2

=
24
(k + 1) {2(k + 2k + 1) + 9(k + 1) + 13}
2

=
24
(k + 1) {2(k + 1) + 9(k + 1) + 13}
2

=
24
∴ Sk +1 is true
∴ Sn is true ∀n ∈ N

n(n + 1) 2 (n + 2)
12. 12 + (12 + 22 ) + (12 + 22 + 33 ) + .......... up to n terms =
12
n(n + 1) 2 (n + 2)
Sol: 12 + (12 + 22 ) + (12 + 22 + 32 ) + ........ + (12 + 22 + 32 + .....n 2 ) =
12
n(n + 1)(2n + 1) n(n + 1) (n + 2)
2
12 + (12 + 22 ) + (12 + 22 + 32 ) + ........ = =
6 12
Let S ( n ) be the given statement
For n = 1
L.H.S = 1
1(1 + 1)2 (1 + 2)
R.H.S =
12
Assume Sk is true

www.sakshieducation.com
www.sakshieducation.com
k (k + 1)(2k + 1) k (k + 1) 2 (k + 2)
12 + (12 + 22 ) + (12 + 22 + 32 ) + ... + =
6 12
(k + 1)(k + 2)(2k + 3)
Adding (k + 1)th term i.e. = on both sides
6

(k + 1)(k + 2)(2k + 3) k (k + 1)2 (k + 2) (k + 1)(k + 2)(2k + 3)


12 + (12 + 22 ) + (12 + 22 + 32 ) + .....+ = = +
6 12 6

k (k + 1) 2 (k + 2) + 2(k + 1)(k + 2)(2k + 3)


=
12
(k + 1)(k + 2) {k + k + 4k + 6}
2

=
12
(k + 1)(k + 2) {k 2 + 5k + 6}
=
12
(k + 1)(k + 2) (k + 2) (k + 3)
=
12
(k + 1)(k + 2) 2 (k + 3)
=
12
13. Using mathematical induction, prove the following statements, for all n ∈ N.
⎛ 3 ⎞ ⎛ 5 ⎞⎛ 7 ⎞ ⎛ 2n + 1 ⎞
⎜1 + ⎟ + ⎜1 + ⎟⎜1 + ⎟ ... ⎜1 + 2 ⎟ = (n + 1)
2
⎝ 1 ⎠ ⎝ 4 ⎠⎝ 9 ⎠ ⎝ n ⎠

7 ⎞ ⎛ 2n + 1 ⎞
Sol. Let S(n): ⎛⎜1 + 3 ⎞⎟ + ⎛⎜1 + 5 ⎞⎛
⎟⎜1 + ⎟ ... ⎜1 + 2 ⎟ = (n + 1) be the given statement.
2
⎝ 1⎠ ⎝ 4 ⎠⎝ 9⎠ ⎝ n ⎠

Let n=1
L.H.S. = 1 + 3 = 4
R.H.S = (1 + 1)2 = 22 = 4
L.H.S. = R.H.S.
Therefore, S(1) is true.
Let us assume that S(k) is true.

⎛ 3 ⎞ ⎛ 5 ⎞⎛ 7 ⎞ ⎛ 2k + 1 ⎞
i.e. ⎜1 + ⎟ + ⎜1 + ⎟ ⎜1 + ⎟ ......... ⎜ 1 + 2 ⎟ = (k + 1) 2
⎝ 1 ⎠ ⎝ 4 ⎠⎝ 9 ⎠ ⎝ k ⎠
To prove S(k + 1) is true.
We know that (k + 1)th factor is :

2(k + 1) + 1 ⎡ 2k + 3 ⎤
1+ = ⎢1 + 2⎥
(k + 1) 2
⎣ (k + 1) ⎦
⎛ 3 ⎞⎛ 5 ⎞⎛ 7 ⎞ ⎛ 2k + 1 ⎞
Consider ⎜1 + ⎟⎜1 + ⎟⎜1 + ⎟ ......... ⎜1 + 2 ⎟ = (k + 1) 2
⎝ 1 ⎠⎝ 4 ⎠⎝ 9 ⎠ ⎝ k ⎠
⎛ 2k + 3 ⎞
Multiplying both sides by ⎜1 + 2 ⎟
⎝ (k + 1) ⎠
www.sakshieducation.com
www.sakshieducation.com

⎛ 3 ⎞⎛ 5 ⎞⎛ 7 ⎞ ⎛ 2k + 1 ⎞ ⎛ 2k + 3 ⎞
⎜1 + ⎟ ⎜1 + ⎟ ⎜ 1 + ⎟ ......... ⎜1 + 2 ⎟ ⎜1 + ⎟
⎝ 1 ⎠⎝ 4 ⎠⎝ 9 ⎠ ⎝ k ⎠ ⎝ (k + 1) 2 ⎠
⎛ 2k + 3 ⎞
= (k + 1) 2 ⎜1 + 2 ⎟
⎝ (k + 1) ⎠
⎡(k + 1) 2 + 2k + 3⎤
= (k + 1) ⎣2 ⎦
(k + 1) 2

= k 2 + 1 + 2k + 2k + 3
= k 2 + 4k + 4
2
= (k + 2) 2 = ⎡⎣ (k + 1) + 1⎤⎦
Thus S(k + 1) is true
By the principle of mathematical induction S(n) is true for all n ∈ N.

14. If x and y are natural numbers and x ≠ y, using mathematical induction show that
xn – yn is divisible by x – y for all n ∈ N.
Sol. Let S(n): xn – yn is divisible by x – y be the given statement.
Put n = 1, x1 – y1 = x – y
xn – yn is divisible by x – y
∴ S(1) is true for n = 1
Put n = k, xk – yk = (x – y)p (∵ p is an integer)
∴ xk – yk = (x – y)p …(1)
S(k) is true for n = k
We know that,

x k +1 − y k +1 = x k +1 − x k y + x k y − y k +1
= x k ⋅ x − x k y + x k y − yk ⋅ y
= x k (x − y) + y(x k − y k )
= x k (x − y) + y(x − y)p (∵ from(1))
= (x − y)(x k + yp)
= (x − y)q (∵ q is an integer)

Since p is a polynomial in x and y, so is q.


Hence xk+1 – yk+1 is divisible by (x – y)
∴ S(k + 1) is true for n = k + 1

By the principle of mathematical induction, S(n) is true for all n ∈ N.

www.sakshieducation.com
www.sakshieducation.com
15. Show that 49n + 16n – 1 is divisible by 64 for all positive integers n.
Sol. Let S(n): 49n + 16n – 1 is divisible by 64 be the statement.
Since 491 + 16.1 – 1 = 64 is divisible by 64.
∴ S(n) is true for n = 1
Assume that the statement S(n) is true for n = k
i.e. 49n + 16n – 1 is divisible by 64
Then 49k + 16k – 1 = 64 M …(1) (∵ M is an integer)
We show that the statement S(n) is true for n = k + 1
i.e. we show that 49k+1 + 16(k+1) – 1 is divisible by 64.
From (1), we have
49k + 16k – 1 = 64 M
49k = 64 M – 16k + 1
49k × 49 = (64 M – 16k + 1) × 49
49k+1 + 16(k + 1) – 1 = (64M – 16k + 1)49 + 16(k + 1) – 1
= 64× 49 M – 49 × 16k + 49 + 16k + 16 – 1

= 64 × 49 M – 48 × 16k + 64

= 64 × 49 M – 64 × 12k + 64
= 64(49 M – 12k + 1)
= 64 N [∵ N is an integer]
∴ S(n) is true for n = k + 1

∴ By the principle of mathematical induction, S(n) is true for all n ∈ N.

www.sakshieducation.com